Nursing education: mapping in the perspective of transformation - Josicelia Dumêt Fernandes; Rosana Maria de Oliveira Silva; Giselle Alves da Silva Teixeira; Raíssa Millena Silva Florêncio; Lázaro Souza da Silva; Carolina Marques Freitas
ABSTRACT Objective: to construct a theoretical, field and analysis mapping of nursing education in the context of public education policies in Brazil. Method: a descriptive study with a mixed approach of investigation, having as theoretical-analytical instruments the studies on maps construction (theoretical, field and analytical), which allowed the distribution, imbalances, tendencies and contradictions verification of the phenomenon studied. Results: the disordered expansion of vacancies in nursing has been occurring in a disorganized, asymmetric way and directed to the distancing of the State in the assistance to the educational sector, as well as the consequent privatization of education and reaffirmation of social imbalance of regions with the lowest economic power. Final considerations: the study made technological, scientific and academic contributions possible and showed that public policies directed intense and disorderly expansion of courses/vacancies, indicating the need to establish strategies that can promote actions to strengthen the quality of nursing education.